2005
DOI: 10.1254/jphs.fpj05025x
|View full text |Cite
|
Sign up to set email alerts
|

Milk Whey Culture With Propionibacterium freudenreichii ET-3 Is Effective on the Colitis Induced by 2,4,6-Trinitrobenzene Sulfonic Acid in Rats

Abstract: Abstract. This study aimed to evaluate whether milk whey culture with Propinibacterium freudenreichii ET-3 (milk whey culture), which has been reported to have Bifidogenic activity, is effective on the colitis induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS) in rats. For the induction of colitis, the colon was clamped and 0.1 M TNBS in 35% ethanol was injected into the luminal side of the clamped portion under pentobarbital anesthesia. From the next day of colitis induction, milk whey culture was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…By contrast, some P. freudenreichii strains produce a surface beta-glucan exopolysaccharide after growth in a dairy-based medium and display no immunomodulatory properties, while the mutational inactivation of this exopolysaccharide capsule leads to anti-inflammatory properties of the mutant strains (Deutsch et al , 2012. Accordingly, pure cultures of P. freudenreichii ET-3 in whey exerted protective effects in experimental colitis in mice (Okada et al 2006;Uchida and Mogami 2005). A pilot clinical study on ulcerative colitis also suggests a beneficial effect of this strain in humans (Suzuki et al 2006).…”
Section: Immunomodulation By Dairy Bacteriamentioning
confidence: 99%
“…By contrast, some P. freudenreichii strains produce a surface beta-glucan exopolysaccharide after growth in a dairy-based medium and display no immunomodulatory properties, while the mutational inactivation of this exopolysaccharide capsule leads to anti-inflammatory properties of the mutant strains (Deutsch et al , 2012. Accordingly, pure cultures of P. freudenreichii ET-3 in whey exerted protective effects in experimental colitis in mice (Okada et al 2006;Uchida and Mogami 2005). A pilot clinical study on ulcerative colitis also suggests a beneficial effect of this strain in humans (Suzuki et al 2006).…”
Section: Immunomodulation By Dairy Bacteriamentioning
confidence: 99%
“…It has been demonstrated that consumption of either isolated BGS or P. freudenreichii strains ameliorate experimental colitis in mice and human ulcerative colitis [171,[189][190][191][192]. The mechanism proposed for this effect was restoring of microbiota intestinal balance and suppressing inflammatory lymphocyte infiltration.…”
Section: Alleviation Of Ibdmentioning
confidence: 99%
“…Dairy propionibacteria display various probiotic properties either similar to or distinct from those reported for probiotic bifidobacteria and lactic acid bacteria (3). Although an anti-inflammatory potential of a few dairy propionibacterium strains was occasionally suggested in vitro (15) or in animals (22,24,31), no reliable observation was established in terms of strain variability and of specific mechanisms involved. In addition, supplementation with dairy propionibacteria in human randomized, placebo-controlled, double-blind trials has mainly concerned mixtures comprising probiotic bacteria assigned to genera other than Propionibacterium but rarely with propionibacteria alone (16).…”
mentioning
confidence: 99%